2010
DOI: 10.3844/ajisp.2010.43.49
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Serum and Semen Malondialdehyde and Total Anti-Oxidants with Sperm Parameters in Infertile Men

Abstract: Problem statement: Oxidative Stress (OS) has been recognized as one of the most important cause of male infertility. We studied the relation of serum and Semen Malondialdehyde (MDA) and Total Antioxidant Capacity (TAC) with sperm parameters in infertile men with sperm count within the normal range. Approach: The prospective case- control study performed on infertile men presenting to the infertility clinics of Mirzakochak khan hospital, Tehran university of Medical Sciences fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Several studies have shown that lipid peroxidation impacts the sperm concentration, motility, morphology and associated with poor sperm quality ( 40 - 42 ) Patel et al observed ( 43 ) the negative correlation between the MDA levels and the normal sperm motility and morphology, so they suggested damaging effect of free radicals on sperm membrane integrity. Asbagh et al ( 44 ) showed that there was significant association between semen MDA and abnormal sperm morphology, and decrease semen TAC and weak sperm motility. Gholinezhad and Hosseinzadeh Colagar6 showed a negative correlation between MDA levels and the motility and morphology of spermatozoa and a positive correlation between the TAC reflected by motility and morphology of spermatozoa in asthenoteratospermic smokers and non-smokers in comparison with a control group.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that lipid peroxidation impacts the sperm concentration, motility, morphology and associated with poor sperm quality ( 40 - 42 ) Patel et al observed ( 43 ) the negative correlation between the MDA levels and the normal sperm motility and morphology, so they suggested damaging effect of free radicals on sperm membrane integrity. Asbagh et al ( 44 ) showed that there was significant association between semen MDA and abnormal sperm morphology, and decrease semen TAC and weak sperm motility. Gholinezhad and Hosseinzadeh Colagar6 showed a negative correlation between MDA levels and the motility and morphology of spermatozoa and a positive correlation between the TAC reflected by motility and morphology of spermatozoa in asthenoteratospermic smokers and non-smokers in comparison with a control group.…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not find any association between smoking and sperm parameters in infertile men (25).…”
Section: Discussionmentioning
confidence: 99%
“…Our study result was similar to the studies done by Colagar et al ., Fazeli and Salimi, and Hosen et al ., and Asbagh et al . [10151617] Excessive oxidative stress in the semen of men with abnormal semen parameters was the reason for higher MDA value.…”
Section: Discussionmentioning
confidence: 99%